Beneficial Effects of Qingzixiaoban Granule on Henoch–Schönlein Purpura Nephritis Mice through Inhibiting Immune Complex Deposition and Th2 Immunodeviation. (16th October 2019) - Yang, Hui; Guan, Jing; Ma, Pei; Fan, Yannan; Bai, Jinye; Li, Shuyi; Yuan, Jiqiao; Jin, Yecheng; Lin, Mingbao; Zhang, Jianmin; Hou, Qi
Abstract : Background . Henoch–Schönlein purpura nephritis (HSPN) is the principal cause of morbidity and mortality in Henoch–Schönlein purpura (HSP). However, there is no absolute consensus for the best management of severe HSPN till now. Qingzixiaoban Granule (QZXB GR), a traditional Chinese medicine formula, has been applied to treat HSP in clinical in China. However, the therapeutic effects and potential mechanism of QZXB GR on HSPN is still unknown. Methods . A Gliadin plus Indian Ink-induced HSPN mice model was established. Renal histopathologic changes and the subcutaneous hemorrhage on left legs were assessed. Hematuria and proteinuria were determined using hemocytometer and bicinchoninic acid assay, respectively. The serum circular immune complex and interleukin-6 were quantified by ELISA. Using blood biochemical analyzer, the renal biochemical parameters, including serum total protein, albumin, creatinine, and blood urea nitrogen, were measured. The deposition of immune complex in renal tissues and the lymphocyte subsets in peripheral blood and spleen was investigated by immunohistochemistry and flow cytometry. Results . QZXB GR treatment significantly ameliorated renal injury in HSPN mice, by attenuating renal histopathological changes, reducing subcutaneous hemorrhage, decreasing proteinuria/hematuria, regulating renal biochemical parameters, and inhibiting the release of serum interleukin-6. Furthermore, QZXB GR treatment significantly decreased the level of serum circular immune complex, decreased immune complex IgA and IgG deposition in renal tissue, and suppressed Th2 immunodeviation. Conclusion . QZXB GR could prevent renal injury in HSPN mice, and its renoprotective mechanism might be exerted partly through suppressing immune complexes deposition and Th2 immune deviation.